2016
DOI: 10.1007/s40268-016-0149-5
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Glucose-Lowering Mechanisms of Ipragliflozin Depending on Body Weight Changes

Abstract: BackgroundSodium-glucose co-transporter 2 inhibitors have been shown to reduce body weight. However, little is known about whether a reduction in body weight affects glycemic and non-glycemic parameters.ObjectivesThe aim of this study was to investigate the link between the changes in body weight and those in metabolic parameters in drug-naïve subjects with type 2 diabetes mellitus (T2DM) receiving ipragliflozin monotherapy.MethodsSubjects received ipragliflozin monotherapy 25–50 mg/day for 3 months (n = 33). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Interestingly, similar glycemic efficacies were seen in subjects with (Group L) or without (Group N) body weight reductions (Table 4a, b). This result implicates that the glycemic efficacy of canagliflozin is not linked to the reductions of body weight as shown with another SGLT-2 inhibitor [5]. However, those who lose weight with canagliflozin may have more advantages than those who do not with respect to some of the non-glycemic parameters, including UA and TG (Table 4a).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Interestingly, similar glycemic efficacies were seen in subjects with (Group L) or without (Group N) body weight reductions (Table 4a, b). This result implicates that the glycemic efficacy of canagliflozin is not linked to the reductions of body weight as shown with another SGLT-2 inhibitor [5]. However, those who lose weight with canagliflozin may have more advantages than those who do not with respect to some of the non-glycemic parameters, including UA and TG (Table 4a).…”
Section: Discussionmentioning
confidence: 73%
“…Sodium-glucose co-transporter 2 (SGLT-2) inhibitors are new oral hypoglycemic drugs for type 2 diabetes mellitus (T2DM) that increase glucose excretion into the urine [13]. Consistent with this mechanism of action, one of the most beneficial non-glycemic properties of SGLT-2 inhibitors is their effect on body weight [4]; however, it is frequently experienced by physicians and patients that body weight reductions of SGLT-2 inhibitors are not always linked to their glycemic efficacies as previously proposed [5].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies of ipragliflozin monotherapy and ipragliflozin add-on to metformin have shown improvements in insulin resistance and β-cell function at the EOT. 14,21 In a study in which patients were treated with ipragliflozin monotherapy, significant reductions in HOMA-IR levels and significant increases in HOMA-β levels from baseline were observed at the end of the 12-week treatment. 21 In another study in patients whose T2DM was inadequately controlled by metformin, addition of ipragliflozin resulted in significant decrease in HOMA-IR levels compared with placebo after 24 weeks of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…14,21 In a study in which patients were treated with ipragliflozin monotherapy, significant reductions in HOMA-IR levels and significant increases in HOMA-β levels from baseline were observed at the end of the 12-week treatment. 21 In another study in patients whose T2DM was inadequately controlled by metformin, addition of ipragliflozin resulted in significant decrease in HOMA-IR levels compared with placebo after 24 weeks of treatment. 14 Other studies of SGLT2 inhibitors also reported a significant decrease in insulin resistance and a significant increase in β-cell function at the EOT.…”
Section: Discussionmentioning
confidence: 99%